2009
DOI: 10.1038/bmt.2009.312
|View full text |Cite
|
Sign up to set email alerts
|

Baseline profiles of ocular surface and tear dynamics after allogeneic hematopoietic stem cell transplantation in patients with or without chronic GVHD-related dry eye

Abstract: We evaluated ocular surface alterations in allogeneic hematopoietic stem cell transplantation (HSCT) recipients with or without chronic GVHD-related dry eye in a prospective study. Fifty eyes of 25 post-HSCT patients and 28 eyes of 14 age-matched healthy controls were included. Meibomian gland (MG) obstruction, tear evaporation rate, corneal sensitivity (CS), Schirmer test-I, tear break-up time (BUT) and ocular surface vital staining were examined. Conjunctival impression and brush cytology specimens were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 30 publications
3
72
1
3
Order By: Relevance
“…In addition to deficient tear production, tear evaporation rate and meibomian gland functions also appear to be significantly compromised in cGVHD. This is in agreement with the inferences drawn in previous studies, 7,8,14 although there are differences in the instrumentation used in the different studies. It is noteworthy that Wang et al 14 did not find a statistically detectable difference between tear evaporation rates of BM transplant recipients with and without cGVHD.…”
Section: Lipid Layer Unstable Stablesupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to deficient tear production, tear evaporation rate and meibomian gland functions also appear to be significantly compromised in cGVHD. This is in agreement with the inferences drawn in previous studies, 7,8,14 although there are differences in the instrumentation used in the different studies. It is noteworthy that Wang et al 14 did not find a statistically detectable difference between tear evaporation rates of BM transplant recipients with and without cGVHD.…”
Section: Lipid Layer Unstable Stablesupporting
confidence: 82%
“…Unquantifiable reflex secretion following the insertion of Schirmer strips makes it difficult to assess the agreement of our findings with previous reports of Schirmer test results in cGVHD. The general trend observed with cGVHD dry eye patients was of low Schirmer test values, 2,7,8,14,20,21 supporting the impairment of tear production in cGVHD-associated dry eye. A histological study has shown that there is a predominant infiltration of T-cells into the periductal area, an increase in the number of stromal fibroblasts and excessive fibrosis in Although no statistically significant differences were found, the data indicates that the tear osmolarity values for cGVHD-associated dry eye are higher than that for the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 18 showed clinical signs of chronic oGvHD. In contrast to earlier research studies [44,45], this study failed to demonstrate a correlation between oGvHD status and HLA-DR expression in conjunctival epithelial cells [12]. The authors did, however, report an association between CD8-stained lymphocytes and oGvHD.…”
Section: Ocular Graft-versus-host Diseasecontrasting
confidence: 55%
“…2 The local therapies most commonly used to reduce ocular inflammation and corneal lesions (corticosteroids, CsA, tacrolimus and others) in association with artificial tears, demonstrated poor tolerance and unsatisfactory response. 3,5,9 For instance, a recent meta-analysis estimated that topical lubricants provide an overall improvement that is no greater than 25% from baseline, while topical CsA achieved improvement in only 10/16 (62%) patients. 10,11 Recently, borrowing from the experience of patients with severe DES in Sjö gren's disease, 12,13 treatment with autologous serum eye drops has been proposed to treat refractory keratoconjuntivitis sicca in GVHD patients with good results, demonstrating that serum is safe and effective in the majority of patients after 4 weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%